Synthesis and Characterizations of Dipeptide Derivative of Gentamicin - Khudair, oun D.; A. Fatih, Diar (Iraqi Journal of Pharmaceutical Sciences, 2019)
Abstract The target derivative are gentamicin linked with L-Val- L-Ala by an ester linkage. These were synthesized by esterification method, which included the reaction of -OH hydroxyl group on (carbon No.5) of gentamicin with the acid chloride of the corresponding dipeptide, The preparation of new derivative of gentamicin involved protected the primary & secondary amine groups of Gentamicin, by Ethylchloroformate (ECF) to give N-carbomethoxy Gentamicin which was used for further chemical synthesis involving the free hydroxyl groups. Then prepared dipeptide (L-Val- L-Ala) by conventional solution method in present DCC & HoBt then reacted with thionyl chloride to prepared acid chloride of dipeptides, then after, linked by ester linkage to N-protection gentamicin in present pyridine as base, finally deportation the amino group of synthesized compound by using TFAA in present anisole. The characterization of the titled compounds were performed utilizing FTIR spectroscopy, CHNS elemental analysis, and by measurements of their physical properties.